Design Of Cathodic Protection For Ship’s Hulls Using Sacrificial Anodes - أحمد غالب (Latakia University Journal -Engineering Sciences Series, 2020)
To minimize the risk of failures or major renewals of hull structures during the ship’s expected life span, It is imperative that the precaution must be taken with regard to an adequate margin of safety against any one or combination of failure modes including excessive yielding, buckling, brittle fracture, fatigue and corrosion. The most efficient system for combating underwater corrosion is ’cathodic protection’. This paper focuses on the sacrificial anode use as a method of cathodic protection of ship’s hulls. The basic principle of this method is that the ship’s hull structure is made cathodic, with respect to another metal acts as anode, the anodic reactions are suppressed on the protected structure. The sacrificial anodes are attached to the hull surface, the electrical current passes from anode to hull due to the difference of potential between the anodes and hull metals. Then, the ship’s hull is protected by converting it to a cathode. The sacrificial anodes are designed to protect the ship’s hull against corrosion until the time of Periodical dry docking, which is between 2 to 3 years. In this design, the required protection is achieved by determining the total weight of sacrificial anodes and output of total electrical current requirements.